1998
DOI: 10.1523/jneurosci.18-14-05508.1998
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Ataxin-1 Display Learning Deficits and Decreased Hippocampal Paired-Pulse Facilitation

Abstract: Spinocerebellar ataxia type 1 (SCA1) is a neurodegenerative disorder characterized by ataxia, progressive motor deterioration, and loss of cerebellar Purkinje cells. To investigate SCA1 pathogenesis and to gain insight into the function of the SCA1 gene product ataxin-1, a novel protein without homology to previously described proteins, we generated mice with a targeted deletion in the murine Sca1 gene. Mice lacking ataxin-1 are viable, fertile, and do not show any evidence of ataxia or neurodegeneration. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(121 citation statements)
references
References 35 publications
4
112
1
Order By: Relevance
“…It could be due to the near complete absence of ATXN1 in transduced cells, although we think this is not likely due the fact that chronic, 100% loss of Atxn1 in mice causes transcriptional misregulation but no noted neuropathology or ataxia. 27,28 A second possibility is that the high level expression of miS1 somehow causes toxicity due to abnormal processing of endogenous miRNAs. This can be evaluated in future work to examine endogenous miRNA processing and miRNA activity.…”
Section: Discussionmentioning
confidence: 99%
“…It could be due to the near complete absence of ATXN1 in transduced cells, although we think this is not likely due the fact that chronic, 100% loss of Atxn1 in mice causes transcriptional misregulation but no noted neuropathology or ataxia. 27,28 A second possibility is that the high level expression of miS1 somehow causes toxicity due to abnormal processing of endogenous miRNAs. This can be evaluated in future work to examine endogenous miRNA processing and miRNA activity.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequence (s) The normal function of ATXN1 is still unclear. ATXN1 KO mice display impairments in learning and memory (4). ATXN1 also stimulates ␤-secretase processing of ␤-amyloid precursor protein (11).…”
Section: * This Work Was Supported By the Canadian Institutes For Heamentioning
confidence: 99%
“…First, loss of function of ATXN1 is not the primary cause of toxicity in SCA1 as mice lacking ATXN1 do not show a SCA1-like phenotype (4). Yet loss of function may partially contribute to neuronal dysfunction through transcriptional dysregulation and abnormal protein interactions (5)(6)(7).…”
mentioning
confidence: 99%
“…the phenotype requires the expression of mutant ATXN1 with an expanded repeat tract (13), whereas loss of function of ATXN1 does not cause an SCA1-like phenotype in mice (14). Data revealing that the toxic effects of the disease causing polyglutamine expansion are determined by the context of other domains in the ATXN1 protein suggested that the endogenous normal function and regulation of ATXN1 interactions are critical for pathogenesis.…”
Section: Atxn1 Protein: Function and Relationship To Disease Pathogenmentioning
confidence: 99%